Hydration of ordinary Portland cement and calcium sulfoaluminate cement blends. (February 2015) - Trauchessec, R.; Mechling, J.-M.; Lecomte, A.; Roux, A.; Le Rolland, B.
Abstract: Ordinary Portland cement (OPC) and calcium sulfoaluminate (CSA) cement are two chemically different hydraulic binders. OPC and CSA cement blends can be used to adjust the binder properties for specific applications. The first part of this article compares the compressive strength and hydration products of three blends (85–15, 70–30 and 40–60% of OPC–CSA cement) using two different OPC. CSA cement percentage modifies the hardening speed as well as the hydration mechanisms (hydrates nature and quantity). The composition of OPC has also a significant influence even for the lowest OPC proportion (40% of OPC). In the second part, investigations based on compressive strength and calorimetry analysis indicate that OPC free lime is a key parameter.